Conservation of Major L1 and Variability of Minor L2 Capsid Late Protein Genes in Human Papillomavirus of Indonesia Variants - Sukma Nuswantara; Titik K Prana; Dwi Wulandari; Henni Widyowati; Vera Anzela; Dea Levy; Petrus Cahyadi; Lukas D Tjandra (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Human Papilloma Virus (HPV) has an out standing feature for its vast intraspecies variability. Of all known 100 types or more, 15 t ypes of them are classified as high risk because of their occurrence in more than 95% of cervical cancer cases. Among all genes in their genome, E6 and E7 genes are considered oncogenes and have close relevance with their pathogenicity, whilst L1 and L2 ge nes produce capsid proteins that directly interact with their host receptors. Considering the importance of L1 and L2 in host-receptor relationship, we tried to investigate their molecular variability thereby uncover their specificity as Indonesian variant s. Here we reported about the conservation of L1 minor capsid protein and variability of L2 capsid protein among high-risk types Human Papilloma Virus (HPV). The results indicated that L1 DNA was relatively more conserved than its L2 counterpart Also it was indicated that the middle part of either L1 or L2 CDS‟ showed more DNA variability than those at their upstream sequences. It is concluded that L2 middle sequences are important factors for intraspecific variations found in HPV of Indonesian variants. Keywords: Human Papilloma Virus (HPV), L1 gene, L2 gene, cervical cancer, high risk HPV